Treatment method of ammonia nitrogen wastewater containing heavy metals
By combining photocatalytic cation exchange membrane and electrolysis, the problem of poor removal of heavy metals in ammonia nitrogen wastewater is solved, and the low-energy consumption and low-cost ammonia nitrogen and heavy metals are completely removed, avoiding secondary pollution.
Patent Information
- Application Number
- CN202411446006.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing ammonia nitrogen wastewater treatment methods are not suitable for heavy metal-containing ammonia nitrogen wastewater, and there are problems of high energy consumption, high cost and secondary pollution.
The photocatalytic cation exchange membrane is used to degrade ammonia nitrogen into ammonia nitrogen and heavy metal ions, and the heavy metal ions are reduced at the cathode through electrolysis to form metal element, achieving the complete removal of ammonia nitrogen and heavy metals.
The removal of ammonia nitrogen and heavy metals with low energy consumption and low cost is achieved, which avoids secondary pollution and improves the treatment effect.
Smart Images

Figure CN118954711B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a method for treating ammonia nitrogen wastewater containing heavy metals. Background Art
[0002] Ammonia nitrogen wastewater refers to wastewater containing a large amount of ammonia nitrogen, which is composed of free ammonia (NH3) and ammonium ions (NH4 + ), ammonia nitrogen wastewater mainly comes from metallurgy, chemical industry, electroplating and pharmaceutical industries. In recent years, the lithium battery industry has developed rapidly. In the production process of ternary precursors, heavy metal salts such as copper salts, cobalt salts and zinc salts are required to react with sodium hydroxide or ammonia water. This process will produce a large amount of ammonia nitrogen wastewater containing heavy metals. The heavy metal refers to heavy metal ions such as Cu 2+ 、Co 2 + and Zn 2+ The metal coordination ion formed with NH3, namely Cu(NH3) n 2+ 、Co(NH3) n 2+ and Zn(NH3) n 2+ These metal coordination ions are difficult to be biodegraded and can accumulate step by step in the food chain, causing harm to the health of animals and humans; high concentrations of ammonia nitrogen can lead to eutrophication of water bodies, causing algae outbreaks, consuming oxygen in the water, deteriorating water quality, and affecting the survival of aquatic organisms. In addition, ammonia nitrogen infiltrates into the soil, changing the physical and chemical properties of the soil, affecting soil fertility and microbial survival.
[0003] At present, the main treatment technologies for ammonia nitrogen wastewater include biological denitrification, air stripping, ion exchange, chemical precipitation, and breakpoint chlorination. Since the ammonia nitrogen wastewater produced by the ternary precursor production process contains a large amount of heavy metals, which is not suitable for the survival of microorganisms, the biological denitrification method is limited. The air stripping method is to pass air or steam into the wastewater to transfer the free ammonia in the wastewater to the gas phase. This method is effective for ammonium ions (NH4 +) and heavy metals are not effectively removed; and the ammonia nitrogen removal effect is poor at low temperatures, requiring the introduction of a large amount of steam, which results in high energy consumption. The ion exchange method is to adsorb ammonia nitrogen by exchanging the exchangeable ions attached to the ion exchange resin with ammonia nitrogen. In this method, the ion exchange resin needs to be frequently regenerated and backwashed, which is cumbersome to operate; and the cost of replacing the resin is high. The chemical precipitation method is to purify ammonia nitrogen wastewater by a precipitation reaction between the precipitant and ammonia nitrogen and heavy metals. Among them, the magnesium ammonium phosphate precipitation method is one of the most commonly used methods in the chemical precipitation method. In this method, the precipitant generally needs to be excessive, and secondary pollution problems are difficult to avoid. The breakpoint chlorination method is to add a chlorine-containing oxidant to the wastewater to undergo an oxidation-reduction reaction with ammonia nitrogen to generate nitrogen gas and chloride. In this method, the chloride needs to be further dechlorinated, which is difficult to handle and costly.
[0004] Chinese patent CN101195507A discloses a method for treating ammonia nitrogen wastewater, which includes a carrier and nitrifying bacteria, and uses the diffusion resistance of oxygen to form three regions of anaerobic, anoxic and aerobic inside and outside the carrier, so that nitrifying bacteria and oxygen are used to react with ammonia on the surface of the carrier to perform an oxidation reaction, and the inside of the carrier is subjected to a denitrification reaction using the oxidation reaction product of ammonia under anoxic conditions, thereby achieving single-stage biological denitrification. This patent is a biological nitrification and denitrification method, which is a type of biological denitrification method, but heavy metals can damage the cell membrane structure of microorganisms and interfere with metabolism, so this patent is not suitable for treating ammonia nitrogen wastewater containing a large amount of heavy metals.
[0005] Chinese patent CN115246669A discloses a method for treating ammonia nitrogen-containing wastewater, wherein a bromide ion solution is added to the ammonia nitrogen-containing wastewater to obtain a mixed solution, and the mixed solution is added to an electrolytic reactor for electrolytic treatment. The patent does not mention that it can be used to treat ammonia nitrogen wastewater containing heavy metals; and because Cu 2+ 、Co 2+ and Zn 2+ Will react with NH3 to form the metal coordination ion Cu(NH3) n 2+ 、Co(NH3) n 2+ and Zn(NH3) n 2+ During the electrolysis process, these metal coordination ions need to overcome the ligand NH3 and Cu 2+ 、Co 2+ and Zn 2+ The reduction reaction can only occur when the binding force between them is strong enough, and the reduction reaction is more difficult to occur, so direct electrolysis treatment is more difficult.
[0006] In view of the problem that the existing ammonia nitrogen wastewater treatment methods are not suitable for ammonia nitrogen wastewater containing heavy metals, it is necessary to find a method that can remove ammonia nitrogen and heavy metals at the same time. This method should have the advantages of low energy consumption, low use cost and thorough treatment without secondary pollution. Summary of the invention
[0007] The purpose of the present invention is to provide a method for treating ammonia nitrogen wastewater containing heavy metals. The method uses a photocatalytic cation exchange membrane to degrade ammonia nitrogen and heavy metals, and at the same time guides the heavy metal ions generated after the degradation to undergo a reduction reaction at the cathode, so as to solve the problems of poor heavy metal removal effect, high energy consumption, high cost and secondary pollution in existing ammonia nitrogen wastewater treatment methods.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] The method for treating ammonia nitrogen wastewater containing heavy metals of the present invention comprises the following steps:
[0010] (1) calcining urea once and then adding hydrogen peroxide for secondary calcination to obtain C3N4 nanosheets; modifying the C3N4 nanosheets with a modifier, separating the solid and the liquid after modification, and calcining the obtained solid to obtain modified C3N4 nanosheets; adding a forming agent and the modified C3N4 nanosheets to a polar organic solvent, blending, forming, scraping, and solidifying to obtain a photocatalytic cation exchange membrane;
[0011] (2) A photocatalytic cation exchange membrane is placed in the middle of an electrolytic cell, which is divided into a cathode chamber and an anode chamber. Ammonia nitrogen wastewater containing heavy metals is placed in the anode chamber, and sulfuric acid is placed in the cathode chamber. A light source is used to irradiate the photocatalytic cation exchange membrane to catalyze the degradation of ammonia nitrogen, while at the same time converting the heavy metals complexed with ammonia nitrogen into free heavy metal ions. After the heavy metal ions pass through the photocatalytic cation exchange membrane, they are reduced at the cathode through electrolysis to obtain metal elements.
[0012] The primary calcination temperature is 350-700°C, the primary calcination time is 1.0-7.0h, and the primary calcination heating rate is 5-12°C / min.
[0013] The secondary roasting temperature is 450-650°C, the secondary roasting time is 2.5-4.5h, and the secondary roasting heating rate is 5-12°C / min.
[0014] The ratio of urea to hydrogen peroxide is 20:(2-3), urea is measured in g, and hydrogen peroxide is measured in mL; the mass fraction of hydrogen peroxide is 3-10wt%.
[0015] The modifier is a mixture of coal gangue and sulfuric acid, the molar concentration of sulfuric acid is 0.5-1 mol / L, and the ratio of coal gangue, sulfuric acid and C3N4 nanosheets is (1-2): (1-5): 1; wherein the coal gangue and C3N4 nanosheets are measured in g, and the sulfuric acid is measured in mL.
[0016] The modification temperature is 40-90°C, and the modification time is 30-180min.
[0017] The calcination temperature is 500-550°C, and the calcination time is 1.5-3h.
[0018] The forming agent comprises polyvinylidene fluoride and polyethylene glycol; the ratio of polyvinylidene fluoride, polyethylene glycol, modified C3N4 nanosheets and polar organic solvent is (10-20): (2-5): (0.1-0.3): 100, wherein polyvinylidene fluoride, polyethylene glycol and modified C3N4 nanosheets are measured in g, and the polar organic solvent is measured in mL; the polar organic solvent is one of acetonitrile, dimethyl sulfoxide, N-methylpyrrolidone or N,N-dimethylformamide.
[0019] The blending temperature is 50-90° C., the blending stirring rate is 260-400 r / min, and the blending time is 4-7 h.
[0020] The light intensity of the light source is 5700-5740 μW / cm 2 ; The electrolytic cell voltage is 1-4V; Stirring is maintained in the electrolytic cell at a stirring rate of 100-400r / min.
[0021] Before the forming, the product is heated in an oven at a temperature of 40-70° C. for 8-12 hours.
[0022] The scraping is performed on the glass using a steel knife, the thickness of the steel knife being 15-25µm.
[0023] The solidification is performed by placing the film and the glass into deionized water for solidification, and the temperature of the deionized water is 0-15°C.
[0024] The composition of the ammonia nitrogen wastewater containing heavy metals is as follows:
[0025] The heavy metal is one or more of cobalt, copper or zinc; the ammonia nitrogen concentration is 200-500 mg / L, the cobalt is calculated as cobalt ions, the concentration is 10-30 mg / L, the copper is calculated as copper ions, the concentration is 10-50 mg / L, the zinc is calculated as zinc ions, the concentration is 10-60 mg / L; the solution pH value is 8-12.
[0026] The concentration of sulfuric acid in step (2) is 0.1-1.0 mol / L.
[0027] In the photocatalytic cation exchange membrane, the component that plays a photocatalytic role is C3N4 nanosheets. The photocatalytic mechanism of C3N4 nanosheets is that when the surface of C3N4 nanosheets is hit by photons, the electrons in the valence band absorb the energy of the photons and jump to the conduction band, forming carriers, namely photogenerated electrons (e - ) and photogenerated holes (h + ), these carriers have a high tendency to gain or lose electrons, and they easily migrate to the surface of C3N4 nanosheets to undergo redox reactions with ammonia nitrogen and heavy metals. However, since most of the carriers are generated inside the C3N4 nanosheets and have opposite charges, they are easily recombined when migrating to the surface, resulting in carrier loss, which ultimately reduces the catalytic efficiency of the photocatalytic cation exchange membrane.
[0028] In this regard, we modified the C3N4 nanosheets. The basic idea of the modification is to minimize the probability of carrier recombination on the surface of C3N4 nanosheets and increase the density of carriers. Then, through the surface modification of sulfuric acid, sulfate ions are introduced as electron traps to capture photogenerated electrons and reduce carrier recombination. In addition, coal gangue can undergo acid hydrolysis with sulfuric acid to generate aluminum sulfate and silicate compounds. These compounds are embedded in the surface defects of C3N4 nanosheets, thereby introducing new energy levels in C3N4 and reducing the electron transition energy barrier, making the carriers, i.e., photogenerated electrons (e - ) and photogenerated holes (h + ) are easier to generate, thereby increasing the carrier density.
[0029] In addition, polyvinylidene fluoride (PVDF) has good mechanical strength, thermal stability and acid and alkali resistance, and can be used as the matrix of photocatalytic cation exchange membranes; and polyethylene glycol (PEG), as a commonly used dispersant, can promote the uniform distribution of PVDF and modified C3N4 nanosheets in polar organic solvents, prevent agglomeration or precipitation, and make the final film have better roughness and porosity.
[0030] The present invention prepares a photocatalytic cation exchange membrane using C3N4 nanosheets with photocatalytic function, and uses ultraviolet rays to irradiate the photocatalytic cation exchange membrane to decompose the ammonia nitrogen contained in the ammonia nitrogen wastewater in the anode chamber into N2 and H2O, and at the same time dissociate the heavy metal ions complexed with the ammonia nitrogen into heavy metal ions Cu 2+ 、Co 2+ and Zn 2+ , and then under the action of the electric field force, these heavy metal ions can selectively pass through the photocatalytic cation exchange membrane into the cathode chamber, obtain electrons in the cathode chamber, turn into metal elements and deposit on the electrode surface, thereby realizing the recovery of heavy metal pollutants in the form of elements; while anions cannot pass through the photocatalytic cation exchange membrane, so that the wastewater in the anode chamber is purified.
[0031] The specific reactions involved are as follows:
[0032]
[0033] The beneficial effects of the present invention are as follows:
[0034] (1) The hydrogen ions in sulfuric acid can react with the amino groups (-NH2) on the surface of C3N4 nanosheets to form -NH3 + ; At this time, sulfate ions can react with -NH3 + Through electrostatic interaction, the sulfate ions are grafted onto the surface of C3N4 nanosheets, which improves the hydrophilicity of the surface of C3N4 nanosheets, allowing water-soluble substances such as ammonia nitrogen and heavy metals to further contact with C3N4 nanosheets and promote the interfacial reaction. On the other hand, sulfate ions have a high electron affinity, so they can act as electron traps to capture photogenerated electrons (e - ), reducing the photogenerated electrons (e - ) and photogenerated holes (h + ) to improve the photocatalytic performance.
[0035] (2) Coal gangue can react with sulfuric acid to produce aluminum sulfate and silica compounds. The silicon dioxide formed during the calcination process can be used as a carrier of C3N4 nanosheets to prevent polymerization. In addition, sulfuric acid improves the hydrophilicity of the surface of C3N4 nanosheets, so these compounds are more likely to spread on the surface of C3N4. By coordinating with lone pairs of electrons in hydroxyl and amino groups on the surface of C3N4 or electrostatically attracting them, they are embedded in the surface lattice defects, thereby changing the energy band structure of C3N4 and introducing new energy levels in C3N4. These new energy levels are located between the original valence band and conduction band of C3N4, which reduces the band gap width, that is, reduces the energy required for transition, making it easier for carriers to be generated. However, a too narrow band gap will also increase the recombination rate of photogenerated electrons and photogenerated holes. In the present invention, since the Al element is embedded in the lattice defects on the surface, the problem of too narrow a band gap caused by uneven distribution of doping elements and excessive doping amount during the doping process is effectively avoided, thereby effectively improving the photocatalytic performance.
[0036] (3) The present invention utilizes a photocatalytic cation exchange membrane to convert the metal coordination ion Cu(NH3) n 2+ 、Co(NH3) n 2+ and Zn(NH3) n 2+ Dissociate into heavy metal ions Cu 2+ 、Co 2+ and Zn 2+, and then remove heavy metal ions through electrolysis, which solves the problem that the existing ammonia nitrogen wastewater treatment method has poor treatment effect on heavy metal ions. At the same time, compared with direct electrolysis to remove metal coordination ions, the present invention has lower energy consumption; through the combination of photocatalysis and electrolysis, ammonia nitrogen and heavy metals are converted into nitrogen, water and solid metal elements without secondary pollution; the photocatalytic cation exchange membrane only has the effects of photocatalysis and ion transmission, and has no adsorption function, so there is no need for frequent backwashing and regeneration, and the cost of use is lower. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a scanning electron microscope image of the product after the first calcination in Example 1;
[0038] Figure 2 is a scanning electron microscope image of the C3N4 nanosheet in Example 1;
[0039] Figure 3 This is a scanning electron microscope image of the modified C3N4 nanosheets in Example 1. DETAILED DESCRIPTION
[0040] The present invention is specifically described and illustrated below in conjunction with embodiments.
[0041] Example 1
[0042] 2 kg of urea was placed in a muffle furnace for primary calcination, and the temperature was raised to 550 ° C at a rate of 10 ° C / min, and the temperature was kept for 3 hours to obtain a light yellow porous solid. The light yellow porous solid was secondary calcined in a muffle furnace together with 200 mL of a 5 wt% hydrogen peroxide solution, and the temperature was raised to 500 ° C at a rate of 10 ° C / min, and the temperature was kept for 3.6 hours to obtain C3N4 nanosheets.
[0043] 100 g of C3N4 nanosheets, 100 g of coal gangue powder and 500 mL of 0.5 mol / L sulfuric acid solution were added to a magnetic stirring reactor, stirred at 50 °C for 60 min, filtered, and the obtained solid was placed in a muffle furnace and calcined at 520 °C for 2.2 h to obtain modified C3N4 nanosheets.
[0044] 100 g of polyvinylidene fluoride, 25 g of polyethylene glycol and 2 g of modified C3N4 nanosheets were added into a magnetic stirring reactor together with 1000 mL of N,N-dimethylformamide, and the stirring rate was set to 320 r / min. The mixture was stirred at 70°C for 4 h. After being dried at 60°C in a hot air circulation oven for 10 h, the mixture was poured onto a glass substrate and coated with a 20 µm scraper. After the film was formed, the glass substrate was placed in deionized water at 5°C to solidify into a film, thereby obtaining a photocatalytic cation exchange membrane.
[0045] Prepare an electrolytic cell, and place high-pressure mercury lamps on the left and right sides of the electrolytic cell. Fix the cation exchange membrane on the sieve plate and place it vertically in the middle of the electrolytic cell. The two sides of the electrolytic cell are the cathode chamber and the anode chamber respectively. Put 1000mL of pH value 10, ammonia nitrogen concentration 325mg / L, Cu(NH3) n 2+ Concentration (Cu 2+ Wastewater containing heavy metals (ammonia nitrogen at a concentration of 25 mg / L) was injected into the anode chamber, and 1000 mL of 0.5 mol / L sulfuric acid solution was injected into the cathode chamber.
[0046] The temperature of the electrolytic cell was controlled at 25°C, and the high-pressure mercury lamp and power were turned on at the same time. The light intensity of the high-pressure mercury lamp was 5730 μW / cm 2 , the power supply voltage is controlled at 3V; the stirring speed is controlled at 300r / min, when the Cu 2+ When the concentration is lower than 0.5 mg / L, turn off the power and the high-pressure mercury lamp to obtain purified water.
[0047] The ammonia nitrogen content in the anode chamber is measured using the distillation-titration method:
[0048] Take 20mL of purified water sample from the anode chamber and pour it into a three-necked flask, then add 20mL of sodium hydroxide solution with a molar concentration of 0.05mol / L and shake well; after checking that the airtightness is qualified, heat the three-necked flask to 37℃ and distill for 30min, and pass the resulting distillate into 20mL of deionized water. Add two drops of methyl red-methylene blue mixed indicator to the deionized water, and titrate with hydrochloric acid standard solution until the deionized water changes from green to light pink. According to the volume and concentration of the consumed hydrochloric acid standard solution, calculate the content of ammonium salt in the distillate, and finally obtain the ammonia nitrogen content in the anode chamber of 26.1 mg / L.
[0049] Example 2
[0050] 2 kg of urea was placed in a muffle furnace for primary calcination, and the temperature was raised to 350 ° C at a rate of 5 ° C / min, and the temperature was kept for 7 hours to obtain a light yellow porous solid. The light yellow porous solid was secondary calcined in a muffle furnace together with 200 mL of a 10 wt% hydrogen peroxide solution, and the temperature was raised to 650 ° C at a rate of 12 ° C / min, and the temperature was kept for 2.5 hours to obtain C3N4 nanosheets.
[0051] 100 g of C3N4 nanosheets, 150 g of coal gangue powder and 100 mL of 1 mol / L sulfuric acid solution were added to a magnetic stirring reactor, stirred at 40 °C for 55 min, filtered, and the obtained solid was placed in a muffle furnace and calcined at 550 °C for 1.5 h to obtain modified C3N4 nanosheets.
[0052] 180g of polyvinylidene fluoride, 20g of polyethylene glycol and 1g of modified C3N4 nanosheets were added into a magnetic stirring reactor together with 1000mL of N-methylpyrrolidone, and the stirring rate was set to 400r / min. The mixture was stirred at 50°C for 6h. After being dried at 55°C in a hot air circulation oven for 10h, the mixture was poured onto a glass substrate and coated with a 15µm scraper. After the film was formed, the glass substrate was placed in deionized water at 5°C to solidify into a film, thereby obtaining a photocatalytic cation exchange membrane.
[0053] Prepare an electrolytic cell, and place high-pressure mercury lamps on the left and right sides of the electrolytic cell. Fix the cation exchange membrane on the sieve plate and place it vertically in the middle of the electrolytic cell. The two sides of the electrolytic cell are the cathode chamber and the anode chamber respectively. Put 1000mL of pH value 12, ammonia nitrogen concentration 245mg / L, Co(NH3) n 2+ Concentration (in Co 2+ Wastewater containing heavy metals (ammonia nitrogen at a concentration of 22 mg / L) was injected into the anode chamber, and 1000 mL of 0.1 mol / L sulfuric acid solution was injected into the cathode chamber.
[0054] The temperature of the electrolytic cell was controlled at 25°C, and the high-pressure mercury lamp and power were turned on at the same time. The light intensity of the high-pressure mercury lamp was 5740 μW / cm 2 , the power supply voltage is controlled at 4V; the stirring speed is controlled at 200r / min, when the anode chamber Co of the electrolytic cell 2+ When the concentration is lower than 0.5 mg / L, turn off the power and the high-pressure mercury lamp to obtain purified water.
[0055] The ammonia nitrogen content in the anode chamber was measured by the distillation-titration method in Example 1, and the ammonia nitrogen content was 31.8 mg / L.
[0056] Example 3
[0057] 2 kg of urea was placed in a muffle furnace for primary calcination, and the temperature was raised to 650 ° C at a rate of 12 ° C / min, and the temperature was kept for 2.5 hours to obtain a light yellow porous solid. The light yellow porous solid was secondary calcined in a muffle furnace together with 300 mL of a 3 wt% hydrogen peroxide solution, and the temperature was raised to 450 ° C at a rate of 5 ° C / min, and the temperature was kept for 4.5 hours to obtain C3N4 nanosheets.
[0058] 100 g of C3N4 nanosheets, 200 g of coal gangue powder and 300 mL of 0.8 mol / L sulfuric acid solution were added to a magnetic stirring reactor, stirred at 90 °C for 30 min, filtered, and the obtained solid was placed in a muffle furnace and calcined at 500 °C for 3 h to obtain modified C3N4 nanosheets.
[0059] 200 g of polyvinylidene fluoride, 50 g of polyethylene glycol and 3 g of modified C3N4 nanosheets were added into a magnetic stirring reactor together with 1000 mL of dimethyl sulfoxide. The stirring rate was set to 260 r / min and stirred at 90 °C for 7 h. After drying at 65 °C in a hot air circulation oven for 10 h, the mixture was poured onto a glass substrate and coated with a 25 µm scraper. After the film was formed, the glass substrate was placed in deionized water at 5 °C to solidify into a film to obtain a photocatalytic cation exchange membrane.
[0060] Prepare an electrolytic cell, and place high-pressure mercury lamps on the left and right sides of the electrolytic cell. Fix the cation exchange membrane on the sieve plate and place it vertically in the middle of the electrolytic cell. The two sides of the electrolytic cell are the cathode chamber and the anode chamber respectively. Place 1000mL of pH value 8, ammonia nitrogen concentration 400mg / L, Zn(NH3) n 2+ Concentration (as Zn 2 + Wastewater containing heavy metals (45 mg / L ammonia nitrogen) was injected into the anode chamber, and 1000 mL of 0.5 mol / L sulfuric acid solution was injected into the cathode chamber.
[0061] The temperature of the electrolytic cell was controlled at 25°C, and the high-pressure mercury lamp and power were turned on at the same time. The light intensity of the high-pressure mercury lamp was 5700 μW / cm 2 , the power supply voltage is controlled to 1V; the stirring speed is controlled to 100r / min, when the Zn 2+ When the concentration is lower than 0.5 mg / L, turn off the power and the high-pressure mercury lamp to obtain purified water.
[0062] The ammonia nitrogen content in the anode chamber was measured by the distillation-titration method in Example 1, and the ammonia nitrogen content was 30 mg / L.
[0063] Example 4
[0064] 2 kg of urea was placed in a muffle furnace for primary calcination, and the temperature was raised to 700 ° C at a rate of 10 ° C / min, and kept warm for 1 hour to obtain a light yellow porous solid. The light yellow porous solid was secondary calcined in a muffle furnace together with 300 mL of a 5 wt% hydrogen peroxide solution, and the temperature was raised to 500 ° C at a rate of 10 ° C / min, and kept warm for 3.6 hours to obtain C3N4 nanosheets.
[0065] 100 g of C3N4 nanosheets, 100 g of coal gangue powder and 500 mL of 0.5 mol / L sulfuric acid solution were added to a magnetic stirring reactor, stirred at 50 °C for 180 min, filtered, and the obtained solid was placed in a muffle furnace and calcined at 520 °C for 2.2 h to obtain modified C3N4 nanosheets.
[0066] 160g of polyvinylidene fluoride, 30g of polyethylene glycol and 3g of modified C3N4 nanosheets were added into a magnetic stirring reactor together with 1000mL of acetonitrile, and the stirring rate was set to 320r / min. The mixture was stirred at 70°C for 4h. After being dried in a hot air circulation oven at 60°C for 10h, the mixture was poured onto a glass substrate and coated with a 20µm scraper. After the film was formed, the glass substrate was placed in deionized water at 5°C to solidify into a film, thereby obtaining a photocatalytic cation exchange membrane.
[0067] Prepare an electrolytic cell, and place high-pressure mercury lamps on the left and right sides of the electrolytic cell. Fix the cation exchange membrane on the sieve plate and place it vertically in the middle of the electrolytic cell. The two sides of the electrolytic cell are the cathode chamber and the anode chamber respectively. Place 1000mL of pH value 12, ammonia nitrogen concentration 350mg / L, Cu(NH3) n 2+ Concentration (Cu 2+ 30mg / L, Zn(NH3) n 2+ Concentration (as Zn 2+ Wastewater containing heavy metals (40 mg / L ammonia nitrogen) was injected into the anode chamber, and 1000 mL of 1.0 mol / L sulfuric acid solution was injected into the cathode chamber.
[0068] The temperature of the electrolytic cell was controlled at 25°C, and the high-pressure mercury lamp and power were turned on at the same time. The light intensity of the high-pressure mercury lamp was 5730 μW / cm 2 , the power supply voltage is controlled at 3V; the stirring speed is controlled at 400r / min, when the Cu 2+ Concentration and Zn 2+ When the concentrations are all lower than 0.5 mg / L, turn off the power supply and the high-pressure mercury lamp to obtain purified water.
[0069] The ammonia nitrogen content in the anode chamber was measured by the distillation-titration method in Example 1, and the ammonia nitrogen content was 27.2 mg / L.
[0070] Comparative Example 1
[0071] Without adding coal gangue, the remaining steps were the same as those in Example 1, and the ammonia nitrogen content was measured to be 64.4 mg / L.
[0072] Comparative Example 2
[0073] No sulfuric acid was added, and the remaining steps were the same as in Example 1. The ammonia nitrogen content was measured to be 60.9 mg / L.
[0074] Comparative Example 3
[0075] 500 g of coal gangue was added into the magnetic stirring reactor, and the remaining steps were the same as those in Example 1. The ammonia nitrogen content was measured to be 75.2 mg / L.
[0076] Comparative Example 4
[0077] 2000 mL of 0.5 mol / L sulfuric acid solution was added into the magnetic stirring reactor, and the remaining steps were the same as those in Example 1. The ammonia nitrogen content was measured to be 78.6 mg / L.
[0078] Analysis: Comparative Example 1 does not add coal gangue, and cannot introduce new energy levels in the C3N4 nanosheets; Comparative Example 2 does not add sulfuric acid, and cannot produce the effect of preventing carrier recombination; Comparative Example 3 is to add excessive coal gangue. From the results, the ammonia nitrogen treatment effect of Comparative Example 3 is not good, because the coal gangue that cannot react with sulfuric acid will adhere to the surface of the C3N4 nanosheets, shielding the active sites, resulting in a decrease in photocatalytic performance. Comparative Example 4 is to add excessive sulfuric acid. From the results, the ammonia nitrogen treatment effect of Comparative Example 4 is not good, because the grafting of excessive sulfate groups may cause excessive capture of photogenerated electrons, which means that the photogenerated electrons cannot be effectively released and participate in subsequent reactions, resulting in their accumulation inside the material, but increasing the probability of recombination with photogenerated holes.
[0079] Although the present invention is described in detail by way of embodiments, the present invention is not limited thereto. Without departing from the spirit and substance of the present invention, those skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions should all be within the scope of the present invention.
Claims
1. A method for treating ammonia nitrogen wastewater containing heavy metals, characterized in that: The following steps are involved: (1) calcining urea once and then adding hydrogen peroxide for secondary calcination to obtain C3N4 nanosheets; modifying the C3N4 nanosheets with a modifier, separating the solid and the liquid after modification, and calcining the obtained solid to obtain modified C3N4 nanosheets; adding a forming agent and the modified C3N4 nanosheets to a polar organic solvent, blending, forming, scraping, and solidifying to obtain a photocatalytic cation exchange membrane; (2) Placing a photocatalytic cation exchange membrane in the middle of an electrolytic cell, which is divided into a cathode chamber and an anode chamber, placing heavy metal-containing ammonia nitrogen wastewater in the anode chamber, and placing sulfuric acid in the cathode chamber. Using a light source to irradiate the photocatalytic cation exchange membrane, the ammonia nitrogen is catalyzed to degrade, and at the same time, the heavy metal ions complexed with the ammonia nitrogen are converted into free heavy metal ions. After the heavy metal ions pass through the photocatalytic cation exchange membrane, they are reduced at the cathode through electrolysis to obtain metal elements. The modifier is a mixture of coal gangue and sulfuric acid, and the ratio of coal gangue, sulfuric acid and C3N4 nanosheets is (1-2): (1-5): 1; wherein the coal gangue and C3N4 nanosheets are measured in g, and the sulfuric acid is measured in mL.
2. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The primary calcination temperature is 350-700°C, the primary calcination time is 1.0-7.0h, and the primary calcination heating rate is 5-12°C / min.
3. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The secondary roasting temperature is 450-650°C, the secondary roasting time is 2.5-4.5h, and the secondary roasting heating rate is 5-12°C / min.
4. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The ratio of urea to hydrogen peroxide is 20:(2-3), urea is measured in g, and hydrogen peroxide is measured in mL; the mass fraction of hydrogen peroxide is 3-10wt%.
5. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The molar concentration of sulfuric acid is 0.5-1 mol / L.
6. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 5, characterized in that: The modification temperature is 40-90°C, and the modification time is 30-180min.
7. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The calcination temperature is 500-550°C, and the calcination time is 1.5-3h.
8. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The forming agents are polyvinylidene fluoride and polyethylene glycol; the ratio of polyvinylidene fluoride, polyethylene glycol, modified C3N4 nanosheets and polar organic solvent is (10-20): (2-5): (0.1-0.3): 100, wherein polyvinylidene fluoride, polyethylene glycol and modified C3N4 nanosheets are measured in g, and the polar organic solvent is measured in mL; the polar organic solvent is one of acetonitrile, dimethyl sulfoxide, N-methylpyrrolidone or N,N-dimethylformamide.
9. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The blending temperature is 50-90°C, the blending stirring rate is 260-400r / min, and the blending time is 4-7h.
10. The method for treating ammonia nitrogen wastewater containing heavy metals according to claim 1, characterized in that: The light intensity of the light source is 5700-5740μW / cm 2 ; The electrolytic cell voltage is 1-4V; Stirring is maintained in the electrolytic cell at a stirring rate of 100-400r / min.
